In vitro selection of Plasmodium falciparum Pfcrt and Pfmdr1 variants by artemisinin. (December 2016) - Njokah, Muturi; Kang'ethe, Joseph; Kinyua, Johnson; Kariuki, Daniel; Kimani, Francis
Abstract Background Anti-malarial drugs are the major focus in the prevention and treatment of malaria. Artemisinin-based combination therapy (ACT) is the WHO recommended first-line treatment forPlasmodium falciparum malaria across the endemic world. Also ACT is increasingly relied upon in treatingPlasmodium vivax malaria where chloroquine is failing. The emergence of artemisinin drug-resistant parasites is a serious threat faced by global malaria control programmes. Therefore, the success of treatment and intervention strategies is highly pegged on understanding the genetic basis of resistance. Methods Here, resistance inP. falciparum was generated in vitro for artemisinin to produce levels above clinically relevant concentrations in vivo, and the molecular haplotypes investigated. Genomic DNA was extracted using the QIAamp mini DNA kit. DNA sequences ofPfk13, Pfcrt andPfmdr1 genes were amplified by PCR and the amplicons were successfully sequenced. Single nucleotide polymorphisms were traced by standard bidirectional sequencing and reading the transcripts against wild-type sequences in Codon code Aligner Version 5.1 and NCBI blast. Results Exposure of parasite strains D6 and W2 to artemisinin resulted in a decrease in parasite susceptibility to artemisinin (W2 and D6) and lumefantrine (D6 only). The parasites exhibited elevated IC50s to multiple artemisinins, with >twofold resistance to artemisinin; however, the resistance index obtained with standard methods was noticeably less than expected for parasite lines recovered from 50 µg/ml 48 h drug pressure. The change in parasite susceptibility was associated withPfmdr -185K mutation, a mutation never reported before. ThePfcrt -CVMNK genotype (Pfcrt codons 72–76) was retained and notably, the study did not detect any polymorphisms reported to reduceP. falciparum susceptibility in vivo in the coding sequences of thePfk13 gene. Discussion This data demonstrate thatP. falciparum has the capacity to develop resistance to artemisinin derivatives in vitro and that this phenotype is achieved by mutations inPfmdr1, the genetic changes that are also underpinning lumefantrine resistance. This finding is of practical importance, because artemisinin drugs in Kenya are used in combination with lumefantrine for the treatment of malaria. Conclusion Artemisinin resistance phenotype as has been shown in this work, is a decrease in parasites susceptibility to artemisinin derivatives together with the parasite's ability to recover from drug-induced dormancy after exposure to drug dosage above the in vivo clinical concentrations. The study surmises thatPfmdr1 may play a role in the anti-malarial activity of artemisinin.